Planetary protection for Europa radar sounder antenna. Issue 9 (1st May 2016) - Aaron, Kim M.; Moussessian, Alina; Newlin, Laura E.; Willis, Paul B.; Chen, Fei; Harcke, Leif J.; Chapin, Elaine; Jun, Insoo; Gim, Yonggyu; McEachen, Michael; Allen, Scotty; Kirchner, Donald; et al.
Abstract: The potential for habitability puts stringent requirements on planetary protection for a mission to Europa. A long-wavelength radar sounder with a large antenna is one of the proposed instruments for a future Europa mission. The size and construction of radar sounding antennas make the usual methods of meeting planetary protection requirements challenging. This paper discusses a viable planetary protection scheme for an antenna optimized for Europa radar sounding. The preferred methodology for this antenna is exposure to 100 kGy (10 Mrad) in water of gamma radiation using a Cobalt-60 source for both bulk and surface sterilization and exposure to vapor hydrogen peroxide for surface treatment for possible recontamination due to subsequent handling. For the boom-supported antenna design, selected tests were performed to confirm the suitability of these treatment methods. A portion of a coilable boom residual from an earlier mission was irradiated and its deployment repeatability confirmed with no degradation. Elasticity was measured of several fiberglass samples using a four-point bending test to confirm that there was no degradation due to radiation exposure. Vapor hydrogen peroxide treatment was applied to the silver-coated braid used as the antenna radiating element as it was the material most likely to be susceptible to oxidative attack under the treatment conditions. There was no discernable effect. These tests confirm that the radar sounding antenna for a Europa mission should be able tolerate the proposed sterilization methods.